1991
DOI: 10.1103/physrevb.44.4560
|View full text |Cite
|
Sign up to set email alerts
|

CuK-edge polarized x-ray-absorption near-edge structure ofBi2CaSr2<

Abstract: The linearly polarized Cu K-edge x-ray-absorption near-edge structure (XANES) of Bi~Sr2CaCu20g+g (Bi 2:2:1:2)has been measured, and the spectra are interpreted by the multiple-scattering approach in real space. The polarized spectra can be predicted in terms of a one-electron dipole (hl =+1)transition Cu 1s~ep, probing the unoccupied p-like (l = 1) density of states projected on the Cu site with orbital angular momentum m, =O in the E~~z spectra, and the m&=1 in the Etc spectra. Therefore we show that the elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 43 publications
2
11
0
Order By: Relevance
“…The third peak mixes Cu 4p mainly with second and third neighbour lanthanum 5f. For these peaks Guo et al [31] showed that the one-electron approximation is valid, the results of Li et al [32] agree with them and partly with those of Bianconi et al [33]. This explains the origin of the three main features of the a, b plane absorption (structures D1, D2, and D3 in Fig.…”
Section: Interpretation Of the Xanes Of 2212 And 2223supporting
confidence: 57%
See 1 more Smart Citation
“…The third peak mixes Cu 4p mainly with second and third neighbour lanthanum 5f. For these peaks Guo et al [31] showed that the one-electron approximation is valid, the results of Li et al [32] agree with them and partly with those of Bianconi et al [33]. This explains the origin of the three main features of the a, b plane absorption (structures D1, D2, and D3 in Fig.…”
Section: Interpretation Of the Xanes Of 2212 And 2223supporting
confidence: 57%
“…From the works of Kosugi et al [34] and Bair et al [35] we know that a shake-down transition occurs at lower energy from the Cu target explaining the B feature. More recently, Li et al [32] and Bianconi et al [33] by a full multiple scattering analysis suggested that B was not a shake-down process but a one-electron transition to a delocalized state over a large cluster. This could be an explanation of the variation of the S / C ratio (see Fig.…”
Section: Interpretation Of the Xanes Of 2212 And 2223mentioning
confidence: 99%
“…A closer comparison between both polarized spectra of the pristine Bi2212 reveals that the features B and C have higher energies with respect to the peaks B and C corresponding to the in-plane transitions, respectively. This observation can be explained by taking into account the local structure of Bi where there is a much shorter (Bi}O 1 ) axial bond (&1.9 A > ) with respect to the other bonds, resulting in the destabilization of d VX , d WX , and d X orbitals (11,26). On the basis of these assignments, we have examined the evolution of Bi electronic structure upon HgBr intercalation by comparing the spectra for the pristine Bi2212 and its HgBr intercalate.…”
Section: Resultsmentioning
confidence: 94%
“…A l and A 2 are characteristic features of the spectrum measured in the out of plane geometry while B 1 and B 2 are observed in the in-plane polarized spectrum. Physical origin of the XANES features has already been discussed (Bianconi et al, 1991). The main absorption features in the powder spectrum are due to complex multiple scattering of the photoelectron excited from the Cu ls core levels.…”
Section: Resultsmentioning
confidence: 91%